WORKING WHILE STUDYING AT UNIVERSITY IN THE SELF- MANAGEMENT PERSPECTIVE: AN ETHNOGRAPHIC STUDY ON JAVA ETHNIC EMPLOYEES - Santoso, Priyono Budi; Asbari, Masduki; Purwanto, Agus; Wijayanti, Laksmi Mayesti; Hyun, Choi. Chi; Maesaroh, Siti; Fayzhall, Miyv; Chidir, Gusli; Mustofa; Hutagalung, Dhaniel; Yani, Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
Working while in college or college while working is not new among employee students. Various reasons have become the reasons behind it. The challenge for student employees is to divide time between college and work. One of the main competencies for successfully performing the role of an employee as well as a student is the ability of self-management. This study aims to examine the perspective of self- management among employees of ethnic Javanese students who work in Kota Seribu Industri Tangerang. This study uses a qualitative approach in scientific situations Kota Seribu Industri Tangerang, Indonesia. The type of research used is ethnography. This research involved 5 respondents. Research data were collected through participant observation, document analysis, in-depth interviews, and focus group discussions (FGD). Ethnographic research is carried out by following the stages and processes of qualitative research that are inductive in nature, consisting of the stages of the developmental research sequence in stages. The results of this study indicate that employees working while studying from ethnic Javanese are able to overcome academic and non-academic problems. Javanese ethnic employees are able to use the methods they deem most effective to regulate themselves (self-management), including the management of feelings (affective), behavior (behavior) and mind (cognitive). The study also concluded that the greatest impetus for Javanese employees to continue their studies was the desire to improve the lives of themselves and their families, in Javanese philosophy is “dadi wong”. The route to achieve this is through the sequence of stages 5E, namely: enjoy, easy, excellence, expert and earn.